2017
DOI: 10.18632/oncotarget.16704
|View full text |Cite
|
Sign up to set email alerts
|

Development of diagnostic SCAR markers for genomic DNA amplifications in breast carcinoma by DNA cloning of high-GC RAMP-PCR fragments

Abstract: Cancer is genetically heterogeneous regarding to molecular genetic characteristics and pathogenic pathways. A wide spectrum of biomarkers, including DNA markers, is used in determining genomic instability, molecular subtype determination and disease prognosis, and estimating sensitivity to different drugs in clinical practice. In a previous study, we developed highly effective DNA markers using improved random amplified polymorphic DNA (RAPD) with high-GC primers, which is a valuable approach for the genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…5'-TAATACGACTCACTATAGGG-3', SP6 primer: 5'-ATTTAGGTGACACTATAGAA-3'), then run on a 1% agarose gel electrophoresis Khan et al 2016;Fu et al 2017).…”
Section: Molecular Cloning and Identification Of Positive Rapd Dna Frmentioning
confidence: 99%
See 1 more Smart Citation
“…5'-TAATACGACTCACTATAGGG-3', SP6 primer: 5'-ATTTAGGTGACACTATAGAA-3'), then run on a 1% agarose gel electrophoresis Khan et al 2016;Fu et al 2017).…”
Section: Molecular Cloning and Identification Of Positive Rapd Dna Frmentioning
confidence: 99%
“…One particularly useful approach, based on initial RAPD sequencing, is Sequence Characterized Amplified Region (SCAR) analysis, which has the advantage of generating markers that are usually very stable and which therefore provides a high level of authenticity in genetic identification Khan et al 2016;Fu et al 2017). By using the SCAR markers, molecular analysis has been simplified to a PCR reaction using PCR primers designed from the sequences of RAPD amplicons (Kumla, et al 2012;Fu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was finally concluded that CPLX2 is a novel clinical biomarker for LNET [26]. In the study of breast cancer diagnostic markers, Fu et al [27] found that changes in gene expression such as DPEP1 may lead to cancer progression. DPEP1 has been identified as a prognostic gene for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a product with 555 bp products was PCR-amplified using gDNA as a template 22. Conventional Sanger sequencing using primer OAT-M212L was conducted to validate suspected pathogenic variants, and a 3500 DX ABI Genetic Analyzer was used for cosegregation analysis of family members.…”
Section: Materials and Methods ‎mentioning
confidence: 99%